Respostas
respondido por:
2
a)f (0)=6. 0^2-0-3=
6. 0-0-3=
0-0-3=-3
b)f (-1)=6. (-1)^2-(-1)-3=
6. 1-(-1)-3=
6+1-3=4
C)f (2)=6. 2^2-2-3=
6. 4-2-3=
24-2-3=19
d) f (1/2)=6. (1/2)^2-1/2-3=
6. 1/4-1/2-3=
6/4-1/2-3= (agr tem que fatorar)
6-2-12(todos os 3) dividido por 4=
-8/4=-2
6. 0-0-3=
0-0-3=-3
b)f (-1)=6. (-1)^2-(-1)-3=
6. 1-(-1)-3=
6+1-3=4
C)f (2)=6. 2^2-2-3=
6. 4-2-3=
24-2-3=19
d) f (1/2)=6. (1/2)^2-1/2-3=
6. 1/4-1/2-3=
6/4-1/2-3= (agr tem que fatorar)
6-2-12(todos os 3) dividido por 4=
-8/4=-2
NatháliaPaschoali:
acredito que seja isso
respondido por:
1
A) 6.(0)2-0-3=6.0-0-3=0-0-3=-3
B) 6.(-1)2-(-1)-3= 6.1+1-3= 6+1-3= 7-3=4
C) 6.(2)2-2-3=6.4-2-3=24-2-3=24-5=19
D) 6(1/2)2-1/2-3= 6.(2/2)-1/2-3= 6.1-1/2-3= 6-1/2-3=
=12/2-1/2-6/2= 5/2
B) 6.(-1)2-(-1)-3= 6.1+1-3= 6+1-3= 7-3=4
C) 6.(2)2-2-3=6.4-2-3=24-2-3=24-5=19
D) 6(1/2)2-1/2-3= 6.(2/2)-1/2-3= 6.1-1/2-3= 6-1/2-3=
=12/2-1/2-6/2= 5/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás